The Effectiveness of the Implementation of Bali Governor Regulation No. 47 of 2019 on Source-Based Waste Management - Putu Eka Trisna Dewi; I Gst. Ag. Laksmi Dwijayanti (Warmadewa Press, 2025)
Bali Governor Regulation No. 47 of 2019 stipulates that producers are obligated to reduce waste by retrieving household waste—and similar types of waste—from products and their packaging for recycling, reuse, and repurposing. In this regard, producers must designate unit waste banks, sector waste banks, and/or main waste banks in each district/city as Temporary Storage Facilities. The approach employed in this empirical legal research is descriptive-analytical. In this study, primary data were obtained from interviews conducted by the author with respondents and informants directly in the field. The respondents comprised members of the community in Kelurahan Ubung. Legal materials were collected through interviews, and the analysis of these materials was carried out using a descriptive qualitative method. The analysis indicates that, prior to the implementation of Bali Governor Regulation No. 47 of 2019, waste management in Kelurahan Ubung faced challenges such as inadequate waste management infrastructure, an unorganized collection system, insufficient waste sorting, and low environmental awareness among the community. However, following the implementation of the regulation, significant improvements were observed in the area. The effective implementation of the regulation has yielded positive outcomes, including enhanced waste management infrastructure, more coordinated and source-based waste management practices, increased environmental awareness among community members, as well as improved waste sorting and recycling. Consequently, the policy has succeeded in enhancing the quality of waste management and in delivering positive impacts on both the environment and the well-being of the community in Kelurahan Ubung.